PENGARUH WAKTU TEKAN DAN UKURAN PARTIKEL KULIT TUSAM (Pinus merkusii Jungh. et. de Vr.) TERHADAP KUALITAS PAPAN PARTIKEL TANDAN KOSONG KELAPA SAWIT - Asfarizal Saad; Anwar Kasim; Gunawarman; Santosa (BRIN Publishing, 2019)
Nowadays binderless particleboards have chance to be developed to replace particleboard with synthetic adhesive. Theobjectve of this research is to determine the quality of particleboards made from oil palm empty fruit bunches (OPEFB)and pine bark waste. The material composition of particleboard consist of 70% OPEFB and 30% pine bark powderwith a moisture content of 5−6%. The fiber length of OPEFB is 0.1−2.0 cm and the pine bark particle sizes usedto produce particleboard which passed through 30, 40, and 50 meshes. Four variations of pressing time are applied toproduce particleboard i.e 10, 15, 20 and 25 minutes. Quality assesments were undergone using the Indonesian standardfor particleboard product: SNI 03-2105-2006. Results showed that the best pressing time for making particleboardsusing OPEFB and pine bark is 20−25 minutes. The best MOR and IB are obtained from particleboard producedfrom oil palm fruit empty bunches with the particle size of 50 mesh. In this condition, except for MOE, the density,moisture content, MOR and IB meet the SNI requirements for particleboard.